Life cycle assessment and eco-efficiency: case in latex concentrate processing - Harahap, S.M; Nik Sulaiman, N.M.; Mahmood, N.Z. (2009)
Demand to natural rubber increased in the last 5 years, this is shown by level of high relative price for rubber market, and still go on up to year 2025. This condition will have potential impact to the environment starting from cultivation process up to the generation industry. Some chemicals must be added to maintain the grade of latex concentrate from natural rubber, energy using and water using which all these will give impact to environment. The impact such as decreased the quality of water body, air emission. Life cycle assessment is a decision making tool to identify environmental burdens and evaluate the environmental consequences of a product, process or service over its life cycle. Eco-efficiency is the path of business and industry can take towards the goal of ecologically sustainable development and links environmental and financial performance. Accounting must be done to know environmental burdens of the activities, and will give an information how eco-efficiency the activities are. The result will show the effect of using chemical and energy in eco-efficiency.